Lignocellulose as raw material in fermentation processes - Mussatto, Solange I. (2010)
Lignocellulose in the form of forestry, agricultural, and agro-industrial wastes is accumulated in large quantities every year. These materials are mainly composed of three groups of polymers, namely cellulose, hemicellulose, and lignin. Cellulose and hemicellulose are sugar rich fractions of interest for use in fermentation processes, since microorganisms may use the sugars for growth and production of value added compounds such as ethanol, food additives, organic acids, enzymes, and others. Submerged and solid-state fermentation systems have been used to produce compounds of industrial interest from lignocellulose, as an alternative for valorization of these wastes and also to solve environmental problems caused by their disposal. When submerged fermentation systems are used, a previous stage of hydrolysis for separation of the lignocellulose constituents is required. This work is an overview about the potential uses of lignocellulosic materials in fermentation processes. Aspects related to submerged and solid-state fermentation systems will be described focusing on the raw materials, hydrolysis processes, fermentation conditions, microorganisms, and products that can be obtained.